ESPAÇO, CARTOGRAFIA E COMUNICAÇÃO: Representações estético-políticas nos mapas de Mona Hatoum - MONTEIRO, ANDRESSA CARAI (2021)
This dissertation aims to understand how the artist Mona Hatoum creates, in her cartographic works, artistic texts, rhizomes and speech genres that articulate with the fields of Communication, Cartography, Aesthetics, Geography, Architecture and the production of different types of representations and uses of cities, spaces, places and landscapes. Hatoum’s cartographies create counter-hegemonic and anti-colonizing narratives that communicate the aesthetic-political relations that individuals and social groups have with their objects and places of belonging. The research focuses on authors who study the construction of cities in contemporary times, such as Lefebvre (1991), Ferrara (2002, 2008, 2015, 2016), Debord (2017); the concepts of space, place, city and landscape, such as Tuan (2012), Pallasmaa (2018), Lefebvre (1991), Navarro (2015) and Ferrara (2012). In addition, will be addressed the concepts of multisensory architecture (PALLASMAA, 2011, 2017, 2018); landscape, visuality and visibility (FERRARA, 2002); aesthetic experience (GUMBRECHT, 2006); virtual and physical body (LÉVY, 2001); an anti-capitalist architecture (KAPP, 2005) and urban drift and wanderings (JACQUES, 2005). We will think of places and the body as communicative and affective devices that produce criticism in the predetermined uses of spaces, making them less spectacular, functional, instrumentalized and commercialized and more ethically and socially equitable (SAWAIA, 2000; SPINOZA, 2008; SALOMANI, 2009). The concepts of place and space will be related to the ideas of identity and memory in everyday architecture (GOLDBERGER, 2011; POLLAK, 1989). Examples of cartographies were gathered that most closely related to the theories proposed in the dissertation and to the definitions of cognitive, affective, sensory, situationist and urban wandering maps. Finally, cartographic processes will be understood as communicational, social, political, aesthetic and cognitive languages (JAMESON, 1996; ACSELRAD, 2010; ROCHA, 2015) and we will present the concepts of rhizome, territorialization and deterritorialization (DELEUZE; GUATARRI, 1995), speech genres and dialogism (BAKHTIN, 1997; VOLÓCHINOV, 2017) and artistic texts and modeling systems (LOTMAN, 1990) so that they can be applied in the hermeneutics analysis of the works of Hatoum Present Tense (1996) and Roadworks (1985).